Translational research for improving the care of familial hypercholesterolemia: The “ten countries study” and beyond - Watts, G.; Ding, P.; George, P.; Hagger, Martin; Hu, M.; Lin, J.; Khoo, K.; Marais, A.; Miida, T.; Nawawi, H.; Pang, J.; Park, J.; et al. (2016)
© 2016 Japan Atherosclerosis Society.Familial hypercholesterolemia (FH) is the most common and serious form of inherited hyperlipidaemia. Dominantly inherited with high penetrance, untreated FH leads to premature death from coronary artery disease due to accelerated atherosclerosis from birth. Despite its importance, there is still a major shortfall in awareness, detection and treatment of FH worldwide. International models of care for FH have recently been published, but their effective implementation requires the garnering of more knowledge about the condition. The “Ten Countries Study” aims to investigate diagnostic, epidemiological and service aspects, as well as physician practices and patient experiences of FH in several countries in the Asia-Pacific Region and the Southern Hemisphere. Five observational studies are being undertaken that will systematically investigate the following aspects of FH: the phenotypic predictors of low-density lipoprotein receptor mutations, the point prevalence in available community populations, current knowledge and clinical practices among primary care physicians, availability and utilisation of services and facilities, and patient perceptions and personal experiences of the condition. The information gathered will inform better clinical practice and will enable the development of country-specific models of care for FH.